The food and nutrition education in question: developments in the initial formation of teacher educators (Research, Society and Development, 2020)
The present work aims to detect, through the State of Question, productions related to the training of teacher educators to work with Food and Nutrition Education (EAN), identifying the theoretical-methodological contributions and the research results. In this investigation, a bibliographic survey was carried out at the Brazilian Digital Library of Theses and Dissertations (BDTD), at the Coordination Portal for Higher Education Personnel Improvement (CAPES) and at the minutes of the National Meeting on Research in Science Education (ENPEC), seeking manuscripts that reported on the organization of curriculum matrices, as well as the preparation of teacher trainers, Pedagogy courses to promote the EAN. At the end of this course, only eight works related to this proposal were detected, in which the theoretical-methodological aspects were identified and a dialogue of the main results was built, covering the organizations of the curricular matrices; scientific and pedagogical conceptions and knowledge of graduates / graduates / teacher trainers of Pedagogy courses for the promotion of EAN. However, despite the contributions of the findings, few productions are still identified in this bias.